Regional Study of the Stø Formation (Toarcian-Bajocian) in and around the area of the Fingerdjupet Subbasin, SW Barents Sea. - Borgenvik, Jørgen Håstø (The University of Bergen, 2021)
Masteroppgave i geovitenskap GEOV399 MAMN-GEOV